2015
DOI: 10.2169/internalmedicine.54.4083
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Time-Course Changes of Reflux Esophagitis in Japanese Patients

Abstract: Objective Obesity is related to an increased prevalence of reflux esophagitis and gastroesophageal reflux disease symptoms. This study was performed to clarify the influence of gender on time-course changes in the rate of a high BMI and incidence of reflux esophagitis in Japanese subjects. Results A multiple logistic regression analysis showed that a high BMI, milder degree of gastric mucosal atrophy and larger size of diaphragmatic hiatus were significant predictive factors for the presence of reflux esophagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
19
1
1
Order By: Relevance
“…53 The percentage of subjects with large hiatal hernias and mild gastric mucosal atrophy were increased in both men and women during the 10-year period. 53 These results suggest that a lack of change in BMI might be a crucial factor for the constant prevalence of reflux esophagitis in Japanese women. 53 In terms of BE, the mean age of women with BE has been reported to be significantly higher than that of men with BE (65.5 ± 15.0 years vs 59.3 ± 13.8 years, P < 0.01) in a large cohort study performed in the Netherlands.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…53 The percentage of subjects with large hiatal hernias and mild gastric mucosal atrophy were increased in both men and women during the 10-year period. 53 These results suggest that a lack of change in BMI might be a crucial factor for the constant prevalence of reflux esophagitis in Japanese women. 53 In terms of BE, the mean age of women with BE has been reported to be significantly higher than that of men with BE (65.5 ± 15.0 years vs 59.3 ± 13.8 years, P < 0.01) in a large cohort study performed in the Netherlands.…”
mentioning
confidence: 94%
“…29 A recent Japanese study using 7670 study subjects (5166 men and 2504 women) who visited a medical center for health check-up has investigated gender differences related to chronological changes in BMI and the prevalence of reflux esophagitis. 53 Multiple logistic regression analysis has revealed that larger hiatal hernia, high BMI, mild gastric mucosal atrophy, and older age were significant positive predictive factors for the presence of reflux esophagitis in both men and women. 53 The number of men with reflux esophagitis and high BMI has increased during the 10-year examination period.…”
mentioning
confidence: 99%
See 3 more Smart Citations